2010
DOI: 10.1593/neo.91972
|View full text |Cite
|
Sign up to set email alerts
|

Small Molecule Inhibitors of Wnt/β-Catenin/Lef-1 Signaling Induces Apoptosis in Chronic Lymphocytic Leukemia Cells In Vitro and In Vivo

Abstract: We have demonstrated that targeting lef-1 is a new and selective therapeutic approach in CLL. CGP049090 or PKF115-584 may be attractive compounds for CLL and other malignancies that deserve further (pre)clinical evaluation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
102
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 112 publications
(115 citation statements)
references
References 31 publications
13
102
0
Order By: Relevance
“…We examined the expression of an expanded set of Wnt pathway members and well-studied targets (supplemental Tables 4 and 5 for the gene list). [20][21][22] Consistent with previous reports, 6,8,9 we found LEF1, a canonical target of the Wnt pathway, to be the most significantly differentially overexpressed messenger RNA in CLL compared with normal B cells (ranked first of 20 765 features, BH-FDR #0.05; supplemental Table 4). We confirmed LEF1 overexpression in CLL cells at the protein level (supplemental Figure 3).…”
Section: The Wnt Pathway Is Transcriptionally and Functionally Hyperasupporting
confidence: 90%
See 2 more Smart Citations
“…We examined the expression of an expanded set of Wnt pathway members and well-studied targets (supplemental Tables 4 and 5 for the gene list). [20][21][22] Consistent with previous reports, 6,8,9 we found LEF1, a canonical target of the Wnt pathway, to be the most significantly differentially overexpressed messenger RNA in CLL compared with normal B cells (ranked first of 20 765 features, BH-FDR #0.05; supplemental Table 4). We confirmed LEF1 overexpression in CLL cells at the protein level (supplemental Figure 3).…”
Section: The Wnt Pathway Is Transcriptionally and Functionally Hyperasupporting
confidence: 90%
“…[6][7][8][9] We confirmed this finding through the comparison of a large gene For personal use only. on May 11, 2018.…”
Section: The Wnt Pathway Is Transcriptionally and Functionally Hyperasupporting
confidence: 76%
See 1 more Smart Citation
“…This is of profound importance given the fact that the Wnt/ b-catenin pathway is aberrantly activated in CLL and contributes to the antiapoptotic and mitogenic nature of B-CLL cells. [70][71][72] In our study, we showed that AEB071 treatment at lower doses mediated GSK3-b dephosphorylation, which correlated with reduced expression of b-catenin as well as its downstream transcriptional targets c-Myc, Cyclin D1, and CD44 at both protein and transcript levels. Given this novel finding, pursuing AEB071 as a therapeutic agent that can target Wnt/b-catenin pathway in CLL is worthwhile and may prove to have significant therapeutic benefit in CLL patients.…”
Section: Org Frommentioning
confidence: 54%
“…Recently, several pharmacological inhibitors or small molecules have been shown to efficiently induce apoptosis of chronic lymphocytic leukemia cells in vitro through their interaction with LEF1. 32,33 These findings implicate that LEF1 may be a potential therapeutic target in the future for patients with chronic lymphocytic leukemia.…”
Section: Discussionmentioning
confidence: 85%